Brazilian Peppertree Seed Wasp, Megastigmus transvaalensis (Hymenoptera: Torymidae) - James P. Cuda; Gregory S. Wheeler; Dale H. Habeck (EDIS)
This document is EENY-270, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2002.